THEORETICAL PERSPECTIVES ON THE STAGES IN THE DEVELOPMENT OF FOLK-BASED DANCE ART UNTIL THE END OF THE 20th CENTURY - Galev, Dilyan (E-Journal VFU, 2025)
The article examines the history of folk dance ensembles in Bulgaria, with a focus on their development as dance schools within the context of economic and cultural processes. Three main periods are outlined, tracing the foundations of folk-based stage dance art, with the first organized formations, as well as the administrative management of amateur artistic activity as fundamental to their development. The significance of the socialist period is also analyzed, during which dance schools became an important element of cultural life, emphasizing mass participation and the preservation of traditional folklore. The article highlights the importance of amateur artistic activity as a means of cultural education and active creative work in society.
Keywords: folk ensemble; artistic director; choreographer; amateur artistic activity; dance group